WANPRESTASI AGEN KORAN PONTIANAK POST DALAM PERJANJIAN KERJASAMA KEMITRAAN DENGAN PT. AKCAYA UTAMA PRESS DI KOTA PONTIANAK - NIM. A1011191177, MUTIA RAHMASARI (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractTo disseminate Pontianak Post to custumers, then the manager or entrepreneur PT. Akcaya Utama Press receives distributors who are tasked to distribute the daily, where before performing the duties, the prospective dealer must meet the requirements specified and then sign the partnership agreement whose contents have been mutually agreed upon. Partnership agreement between Entrepeneur PT. Akcaya Utama Press with a dealer made in writing is intended for the parties to know clearly about the rights and obligations contained in the letter of partnership agreement. If the dealer doesn